Energetics of Ligand Recognition and Self-Association of Bovine β-Lactoglobulin: Differences between Variants A and B - Bello, Martiniano; Portillo-Téllez, María del Carmen; García-Hernández, Enrique (Biochemistry (Easton), 2011)
An understanding of the interplay between structure and energetics is crucial for the optimization of modern protein engineering techniques. In this context, the study of natural isoforms is a subject of major interest, as it provides the scenario for analyzing mutations that have endured during biological evolution. In this study, we performed a comparative analysis of the ligand-recognition and homodimerization energetics of bovine β-lactoglobulin variants A (βlgA) and B (βlgB). These variants differ by only two amino-acid substitutions: 64th (AspA → GlyB), which is fully exposed to the solvent, and 118th (ValA → AlaB), immersed in the hydrophobic core of the protein. Calorimetric measurements revealed significant enthalpic and entropic differences between the isoforms in both binding processes. A structural comparison suggests that a variation in the conformation of the loop C−D, induced by mutation Asp/Gly, could be responsible for the differences in ligand-binding energetics. While recognition of lauric acid was entropically driven, recognition of sodium dodecyl sulfate was both entropically and enthalpically driven, confirming the key role of the ligand polar moiety. Because of a more favorable enthalpy, the dimerization equilibrium constant of βlgB was larger than that of βlgA at room temperature, while the two dimers became similarly stable at 35 °C. The isoforms exchanged the same number of structural water molecules and protons and shared similar stereochemistry at the dimer interface. MD simulations revealed that the subunits of both variants become more flexible upon dimer formation. It is hypothesized that a larger increase of βlgA mobility could account for the dimerization energetic differences observed.